Switching and Fano resonance via exciton-plasmon interaction - 李建波 贺梦冬 王新军 彭小芳 陈丽群 (Chinese physics B, 2014)
We fnrther study theoretically the properties of switching and Fano resonance in a hybrid nanosystem consisting of two quantum dots （QDs） and a metal nanowire via exciton-plasmon interaction. The transmission of the single plasmon can be switched on or off in a wide-frequency region by adjusting the transition frequencies of the QDs and the phase of the propagating plasmon. Specifically, the dynamical mechanism of Fano-type transmission is further revealed and analyzed in detail.